Section based algorithm for image enhancement (2004)
This present invention discloses a system and method for enhancing images of barcodes and other similar objects taken by the digital camera connected to or embedded in a mobile device. This filter works by converting the image into its equivalent gray scale. The algorithm then divides the image into sections and finds the pixels of minimum intensity in each section of the image. This minima is used to calculate cut-off values for thresholding. After thresholding, the image is reassembled from its divided sections.